Overview of karst in Rembang and Blora: their prehistoric cave settlement potential - Hari Wibowo; Indah Asikin Nurani (Berita Sedimentologi, 2021)
Despite the potential of the Rembang zone mountain range is meagre compared to the Kendeng mountain range situated to the south, the Rembang Zone is still known to have archaeological potential. Research in the Rembang Zone in Blora and Rembang regencies have been conducted since 2005. This study aims to reveal the potential for prehistoric cave occupations in the two regencies, which are influenced by karst morphology and lithology. The biggest impact of the morphology and lithology is the lack of caves, rock shelters, or the formation of collapsed doline, which are adequate as prehistoric cave dwellings.